Stakeholder-engaged measure development for pediatric obstructive sleep-disordered breathing: The oSDB and AT knowledge scale for parents - Links, Anne R. (JAMA Otolaryngol Head Neck Surg, 2017)
IMPORTANCE: Parental decision-making about adenotonsillectomy (AT) for obstructive sleep-disordered breathing (oSDB) is associated with decisional conflict that may be alleviated with improved knowledge about symptoms and treatments. OBJECTIVE: To develop a measure of parental knowledge about oSDB and AT. DESIGN: A sequential design was used for scale development. A prototype measure containing 9 oSDB/AT themes and 85 items was administered to oSDB experts and laymen. Quantitative and qualitative responses were used to modify the measure and create the knowledge scale. Content validity of the scale was established through expert feedback and evaluation. Criterion validity was established with t-test comparisons of experts to laymen. Reliability of responses was assessed with Cronbach’s alpha. SETTING: Scale administered in survey format via online (Qualtrics) platform. PARTICIPANTS: Clinician experts (otolaryngologists, pediatricians; n=19) and laymen (parents of children who snore, do not snore, and other adults; n=13). MAIN OUTCOMES AND MEASURES: 85-item prototype measure and 39-item modified measure, evaluated for consensus/approval and psychometric integrity. RESULTS: Content analysis and qualitative feedback were largely positive, although there were several suggestions for rewording and/or addition of response options. Experts identified themes most important for assessing oSDB (symptoms) and AT (experiences: risks; benefits) knowledge. These qualitative comments were used to modify the scale, and items >2 reported as misleading or <85% of clinicians answered correctly were eliminated. 5 themes (oSDB symptoms, treatment options, AT risks, anesthesia, and AT benefits) and 39 items comprised the final scale. Experts scored higher than laymen on the oSDB and AT Knowledge scale overall (94% vs. 67%; d = 1.96, 95% CI [1.05, 2.86]) and within all themes [“Experiences of children with oSDB” ( 88% vs. 62%; d = 1.53, 95% CI [.71, 2.32]), “treatment options” (97% vs. 68%; d = 1.74, 95% CI [.88, 2.57]), “AT risks” (97% vs. 59%; d = 1.94, 95% CI [1.03, 2.83]), “anesthesia” (97% vs. 79%; d = 1.09, 95% CI [.29, 1.88]), “AT benefits”(95% vs. 67%; d = 1.28, 95% CI [.46, 2.09])], demonstrating criterion validity. All responses demonstrated high reliability (α = .93). CONCLUSIONS AND RELEVANCE: The oSDB and AT Knowledge scale is psychometrically sound for use in assessment of parental knowledge.